Ammonia and hydrogen sulfide - new insights into gut microbiota and male infertility through meta-analysis - Hao, Yanan; Du, Xin; Cai, Chang; Zhao, Yong; Ren, Yonglin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundAmmonia (NH3) and hydrogen sulfide (H2S) are produced during digestion in the human gut, yet the impact of these internally generated gases on male reproduction have received limited attention in scientific research.MethodsWe systematically reviewed 935 scientific publications, spanning from 1947 to 2023, focusing on external or internal NH3 and/or H2S, male infertility, and gut microbiota. Meta-analysis was conducted to evaluate the summary relative risk (RR) and 95% confidence intervals (CIs) of combined studies.ResultsOur findings revealed that the internal NH3 and/or H2S were negatively related to the Lactobacillus, which is beneficial to male fertility, whereas NH3 and H2S were positively related to Bacteroides, which showed negative effects on male fertility. The meta-analysis comparing Lactobacillus and Bacteroides levels with NH3 showed statistically significant results (p<0.001).ConclusionsThe meta-analysis is the first to confirm these facts and explored the potential existence of a gut microbiota-inner gases-male fertility axis in the human gut.